IMPLEMENTASI MAJOO DALAM PENYUSUNAN LAPORAN KEUANGAN SAK EMKM PADA THRIFT CAN BE FUN STORE - Febry Ardyanto; Luthfi Hamid Arsyi; Michelle Orpha; Salsabila Irdhiyanti; Yuchriza Sefiana; Zara Tania Rahmadi; Kampono Imam Yulianto; Dias Adhi Dharma; Widjanarko Widjanarko (PUAN INDONESIA, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in Indonesia continue to face significant challenges in managing standardized financial reporting. Thrift Can Be Fun Store, a thrift fashion retail business located at Jl. Raya Krukut No.15, Krukut, Limo District, Depok City, West Java 16514, encountered difficulties in systematic financial recording and in preparing reports in accordance with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). This community service activity aimed to implement the Majoo application as a digital Point of Sale (POS) solution capable of generating SAK EMKM-based financial reports. The method employed was direct mentoring through a series of activities including survey, socialization, training, and evaluation. The results show that the implementation of Majoo successfully recorded total sales of Rp603,867,750.00 with 4,985 products sold across 3,158 transactions during the period of February to April 2026. Of the total transactions, 45.76% were conducted via bank transfer, contributing 56.12% of total revenue, while the remainder used cash payments. The adoption of Majoo proved effective in assisting the partner in compiling product sales reports, payment method reports, and daily transaction records, which serve as the foundation for preparing financial statements in accordance with SAK EMKM standards.